Students’ ability of understanding concepts and computational skill based on learning styles in the discovery learning model - Hapsari, Rania Febri; Kuswardi, Yemi; Andriatna, Riki (Journal of Honai Math, 2025)
Students often face difficulties in both understanding mathematical concepts and performing computations, largely because current teaching methods have not fully supported the development of these skills. This study aims to determine the effect of discovery learning model on conceptual understanding and computational skills based on students' learning styles. This study used a quantitative study with a quasi-experimental design that employed a control group design with a posttest only. This study involved 62 students from a State Junior High School in Sukoharjo Regency, selected through cluster random sampling, with 31 in the experimental group experiencing discovery learning and 31 in the control group receiving direct instruction. Data collection used a test method to measure the ability to understand concepts and computational skills and a questionnaire to categorize students’ learning styles. The data analysis technique used multivariate analysis of variance (MANOVA). The results showed that (1) conceptual understanding and computational skills who were given discovery learning was significantly better than students who were given direct learning; (2) there is no difference in conceptual understanding and computational skills of visual, auditory, and kinesthetic learning style students; (3) in visual, auditory, and kinesthetic learning styles, discovery learning produces better conceptual understanding and computational skills than direct learning; and (4) in discovery learning and direct learing, there is no difference in concept understanding and computational skills of visual, auditory, and kinesthetic learning style students. The results contribute by providing empirical evidence that discovery learning improves students' conceptual understanding and computational skills across different learning styles, providing valuable insights for teachers and curriculum developers in implementing more effective teaching strategies.